One More Time on the Zone of Proximal Development - Zaretsky, V.K. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2021)
Abstract only The article presents an analysis of L.S. Vygotsky’s concept of a zone of proximal development (ZPD); considers various ZPD definitions; provides a critical review of the most popular definition of ZPD as adopted from L.S. Vygotsky’s 1935 work and used as basic by English-speaking authors. Taking into account the fact that L.S. Vygotsky’s general methodological intention was to establish psychology as a practice and that his developmental theory as well as the ZPD concept development remained incomplete due to the known life circumstances, we analyze L.S. Vygotsky’s writings that allow for another ZPD conceptualization, which differs from the one implied by the 1935 definition, so as to attempt at reconstructing the concept. In reviewing L.S. Vygotsky’s assumptions regarding the learning-development relationship; ZPD; its relevance for diagnostic assessment and teaching; feasibility of extrapolating the ZPD concept onto different personality aspects, the authors identify substantive aspects of the ZPD concept that the "canonical" definition lacks. The article describes a multidimensional model of ZPD, which has taken shape within the Reflection-Activity Approach to assisting students with overcoming learning difficulties and which integrates Vygotsky's key ZPD-related ideas. E.G. Yudin’s conceptualization of methodological functions of conceptual schemes is used to reconstruct the methodological status of the ZPD concept. The authors demonstrate that, since its inception, the ZPD concept has passed through the stages of an explanatory principle, a research subject, and a methodological tool for constructing new subjects of research and development. В статье дается анализ понятия зона ближайшего развития (ЗБР) Л.С. Выготского, рассматриваются варианты его определения, проводится критический анализ наиболее распространенного определения ЗБР, взятого из работы Л.С. Выготского 1935 г. и являющегося основным для англоязычных авторов. Исходя из общего методологического замысла Л.С. Выготского о создании психологии-практики и незавершенности его концепции развития, в том числе, незавершенности разработки понятия ЗБР в силу известных жизненных обстоятельств, делается попытка реконструкции понятия на основе анализа различных работ Л.С. Выготского, допускающих возможность иного понимания ЗБР, чем данного в определении 1935 г. В ходе анализа различных положений Л.С. Выготского о связи обучения и развития, о ЗБР, о его значении для диагностики и педагогики, о возможности применения понятия ЗБР к разным сторонам личности устанавливаются содержательные элементы понятия ЗБР, не вошедшие в «каноническое» определение. Дается описание многовекторной модели ЗБР, разработанной в рамках рефлексивно-деятельностного подхода к оказанию помощи учащимся в преодолении учебных трудностей, в которой интегрируются основные идеи Л.С. Выготского о ЗБР. Осуществляется реконструкция методологического статуса понятия ЗБР в опоре на представление о методологических функциях концептуальных схем Э.Г. Юдина. Показано, что с момента своего появления понятие ЗБР проходит стадии объяснительного принципа, предмета исследования и методологического средства построения новых предметов исследований и разработок.